Clinical, Subclinical Characteristics and Classify Urinary Tract Malformation in Children with Urinary Tract Infections at the National Children’s Hospital - Van Dem, Pham; Ngoc Bich, Vu; Thi Phuong, Luong; Thu Huong, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2DO - 10.25073/2588-1132/vnumps.4363, 2022)
Aim: To describe clinical, subclinical characteristics and classify urinary tract malformation in children with urinary tract infections at the National Children’s Hospital.  Subjects and research methods : A cross-sectional descriptive study on 100 children with urinary tract infections and urinary tract malformations treated at the Department of Nephrology and Dialysis of National Children’s Hospital from June 2019 to June 2021.  Results : The rate of malformed urinary tract infections in children accounted for 2.1% of the total urinary tract infections. The male/female ratio was 1.22/1. The most common age was from 3 months to 3 years old (78%). The most common clinical manifestations were fever (89%) and urination disorder (52%). Symptoms of other organs included the digestive system 45%, respiratory system 24%, and nervous system 17%. Children with white blood cell count ≥15 G/L and CRP ≥ 20 mg/L accounted for 60% and 77% respectively. Kidney failure was 11% of children. There was a strong correlation between nitrite-positive and children with positive urine culture (OR: 4.7, Cl95% [1.2-15.2]). Vesicoureteral reflux was the highest observed of urinary malformation of the kidney (78%), followed by the duplex kidney (16%) and ureteropelvic junction narrowing (14%). The rates of recurrence and complications were 59% and 11%, respectively. The rate of recurrent urinary tract infections increased with the severity of reflux. Conclusion : The clinical and subclinical characteristics of urinary tract infections in urinary tract malformations children are most commonly fever, urination disorder, and vesicoureteral reflux get the highest rate.